2020
DOI: 10.5194/bg-17-4883-2020
|View full text |Cite
|
Sign up to set email alerts
|

Do degree and rate of silicate weathering depend on plant productivity?

Abstract: Abstract. Plants and their associated below-ground microbiota possess the tools for rock weathering. Yet the quantitative evaluation of the impact of these biogenic weathering drivers relative to abiogenic parameters, such as the supply of primary minerals, water, and acids, is an open question in Critical Zone research. Here we present a novel strategy to decipher the relative impact of these drivers. We quantified the degree and rate of weathering and compared these to nutrient uptake along the “EarthShape” … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 152 publications
(231 reference statements)
5
24
0
Order By: Relevance
“…More generally, this recycling hypothesis has relevance for the suggestion that plants and associated microbiota impact weathering fluxes (Moulton and others, 2000;Berner and others, 2003;Chaudhuri and others, 2007;Cornelis and others, 2009;Riotte and others, 2014). In agreement with a recent study along a vegetation gradient in Chile (Oeser and von Blanckenburg, 2020a) we find that the large range of nutrient recycling factors, inversely related to erosion rate, buffers ecosystem nutrition making it virtually independent from rock weathering.…”
Section: Nourishing Ecosystems Along An Erodosequencesupporting
confidence: 92%
See 1 more Smart Citation
“…More generally, this recycling hypothesis has relevance for the suggestion that plants and associated microbiota impact weathering fluxes (Moulton and others, 2000;Berner and others, 2003;Chaudhuri and others, 2007;Cornelis and others, 2009;Riotte and others, 2014). In agreement with a recent study along a vegetation gradient in Chile (Oeser and von Blanckenburg, 2020a) we find that the large range of nutrient recycling factors, inversely related to erosion rate, buffers ecosystem nutrition making it virtually independent from rock weathering.…”
Section: Nourishing Ecosystems Along An Erodosequencesupporting
confidence: 92%
“…Regarding weathering and the operation of the global thermostat via CO 2 drawdown, an important consequence is that ecosystems have the ability to buffer mineral nutrient uptake via recycling, and thus weathering rate is not a straightforward function of primary production (Uhlig and von Blanckenburg, 2019;Oeser and von Blanckenburg, 2020a). More specifically, plant growth may not necessarily accelerate rock weathering as suggested in models and syntheses of weathering throughout Earth's history others, 2003, Pagani andothers, 2009).…”
Section: Dee Xmentioning
confidence: 99%
“…6), due to the higher water availability on the NFS (García-Gamero et al, 2021). Oeser & von Blanckenburg (2020) pointed out that the presence of denser vegetation might counteract a potential weathering increase in their study along the climate and vegetation gradient in the Chilean Coastal Cordillera. This could explain why SC8 is not an outlier, similar to SC5.…”
Section: Model Testing and Resultsmentioning
confidence: 99%
“…Similarly, Dixon et al (2016) in their study for chemical weathering in postglacial soils of New Zealand found an important pedogenic threshold coincident at mean annual precipitation of ~800 mm-yr-1, very similar to the threshold value that was identified in this sensitivity analysis. Oeser & von Blanckenburg (2020) on the other hand, in their study in the EarthShape Critical Zone located along the Chilean Coastal Cordillera, found no correlation between the degree of weathering and mean annual precipitation. Therefore, they pointed out that a competitive effect seems to offset the expected increase in the rate of weathering with precipitation.…”
Section: Climatic Effect On Chemical Weathering: Sensitivity Analysismentioning
confidence: 88%
“…Zealand found an important pedogenic threshold coincident at mean annual precipitation of ~800 mm-yr-1, very similar to the threshold value that was identified in this sensitivity analysis. Oeser & von Blanckenburg (2020) on the other hand, in their study in the EarthShape Critical Zone located along the Chilean Coastal Cordillera, found no correlation between the degree of weathering and mean annual precipitation. Therefore, they pointed out that a competitive effect seems to offset the expected increase in the rate of weathering with precipitation.…”
Section: Climatic Effect On Chemical Weathering: Sensitivity Analysismentioning
confidence: 88%